PENGARUH ARUS KAS OPERASI, ARUS KAS INVESTASI, DAN LABA AKUNTANSI TERHADAP RETURN SAHAM DI BEI (STUDI KASUS: PERUSAHAAN PERTAMBANGAN PERIODE 2018 – 2023) - Musafa, Dafa Agil; Jayanti, Fitri Dwi; Nurani, Bulan Karima; Tantra, Arda Raditya (Faculty of Economic and Business Universitas STIKUBANK, 2025)
Background : The capital market plays an important role in the Indonesian economy as an investment vehicle for investors and a source of funding for companies. This study aims to analyze the effect of operating cash flow, investment cash flow, and accounting profit on stock returns in mining subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2023 period. This finding indicates that financial information, especially operating cash flow and accounting profit, can be a reference for investors in making investment decisions. Therefore, companies are advised to increase transparency in financial reports in order to provide a positive signal to investors. Method : The research used a quantitative approach with secondary data obtained from the company's financial statements published on the IDX. The analysis techniques used include descriptive statistical tests, classical assumption tests, and multiple linear regression analysis to test the research hypothesis. Results of the study : Shows that investment cash flow and accounting profit have a significant effect on stock returns, while operating cash flow does not have a significant effect. Simultaneously, operating cash flow, investment cash flow, and accounting profit affect stock returns. Keywords: Operating Cash Flow, Investment Cash Flow, Accounting Profit, Stock Returns, Indonesia Stock Exchange